International competence in Finnish vocational education and training : an analysis of the qualification requirements - Suksi, Emilia (2019)
This Master’s Thesis studies how internationality is expressed in the qualification requirements of Finnish vocational education and training (VET). It explores the use of selected terms and expressions as well as reports their frequencies within the documents. Students of VET need to be equipped for the international world of work which many of them enter upon graduation. This study examines if students can attain international skills through the qualification requirements, in addition to the state of internationality of the qualification requirements. The phenomenon is examined through the conceptual framework of intercultural competence (IC) and analyzed with content analysis. There are altogether 164 qualification requirements out of which 74 are analyzed in detail. The analysis consists of a quantitative and a qualitative section. The quantitative section documents patterns and popularities within the selected expressions and the qualitative section deepens the analysis in exploring the use, meanings, and relations of the expressions. An expert interview is used as support for the inferences made from the analysis of the qualification requirements. Findings showed that direct indications to internationality and culture were overshadowed by expressions of language skills. Nevertheless, they were deemed the most important terms and their use was analyzed in more detail. The analysis revealed that internationality is referred to in traditional ways, and that modern understanding of internationality might not yet be recognized. Under a half of the qualification requirements contain internationality, to varying degrees, and with different emphases.